Interação do peptídeo antimicrobiano L1A com membrana modelo: efeito do pH e carga da vesícula - Viegas, Taisa Giordano [UNESP] (2014)
Antimicrobial peptides have in general short chains, positive net charge due to the excess of basic residues and are rich in hydrophobic amino acids. They have pharmacological potential as antimicrobial agents and their activity is modulated by electrostatic and hydrophobic interactions. In this work, we used the synthetic peptide L1A (IDGLKAIWKKV ADLLKNT NH2) that due to its acid and basic residues have an net charge +3, at neutral pH. The e ects of the pH and of the charges of anionic vesicles on the adsorption of L1A were analized. This study used measurement of electrokinetic potential of vesicles and titration experiments monitored by circular dichroism spectroscopy (CD). Adsorption of L1A to POPC and POPC/POPG LUVs in di erent POPG contents were assessed in the pH 4.0, 7.0 and 10.0. Circular dichroism spectra of the peptides in the presence of vesicles showed to features of helical structures; while random coil structures were observed at bu er for all the used pHs. The helical content was evaluated and showed to increase when the peptide adsorbs into vesicles with increasing amounts of POPG, indicating that there is a strong electrostatic contribution. Partition coe cients were calculated through the normalized CD ellipticities at 222 nm and showed that the a nity of the peptide for anionic model membranes is e ectively higher than those found for zwitterionic ones. It reinforces the importance of the electrostatic contribution to the process of peptide-lipid interaction. The coupled e ect of the vesicle charge and pH lead to signi cant charge regulation of the peptide resulting in high values of e ective charge at pH 4.0 due to the deprotonation of aspartic acid residues. At pH 10.0 the estimated e ective charge is small as a consequence of the deprotonation of both N-terminus and the lysines. The electrostatic and interfatial free energies seems to be additive only at pH 4.0, especially for the bilayers with higher content...